Aplicação de técnicas de árvore de decisão em banco de dados da UHE de Tucuruí - NEVES, Elaine Kelly Nascimento (2018)
This paper presents the concept of data mining and its application to datasets Tucuruí Hydroelectric Plant, in order to perform technical decision tree trying to show that it is possible to apply the technique in Electric Power Systems. The task at hand will be performed on two data sets that are hydrological data and electrical data. The characteristics of the process of Knowledge Discovery in Database and concepts of data mining and decision tree tool of choice for data analysis will be described. Also C4.5 algorithm and its execution characteristics will be presented. The final part of the paper presents the analysis of the results obtained, the conclusions on the application of data mining techniques and the importance of the task of the decision tree for the electric power system.